Tinjauan Yuridis Tindak Pidana Membujuk Anak Melakukan Persetubuhan Yang Dilakukan Oleh Anak (Studi Putusan: No. 2/Pid.Sus.Anak/2021/PN.JNP) - Arry Wirawan; Ambo Esa; Valentina Febrini (Pledoi Law Jurnal, 2023)
ABSTRACT: Children often become victims of sexual crimes. This type of research is normative law research, and the data sources used are primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique used is a literature study (library research) with qualitative data analysis. The research results indicate that (1) the imprisonment sentence imposed on the defendant is based on evidence according to Article 81 paragraph (2) in conjunction with Article 76D of the Republic of Indonesia Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in conjunction with Law Number 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection in conjunction with Law No. 11 of 2012 concerning the Juvenile Justice System. (2) In this case verdict, the panel of judges has considered the grounds for trial and the grounds for decision, where the requirements for imposing criminal sanctions have been fulfilled. ABSTRAK:  Anak-anak sering menjadi korban tindak kejahatan seksual. Kejahatan ini sering dilakukan oleh orang dewasa, terutama dalam bentuk persetubuhan. Jenis penelitian ini adalah hukum normatif, sumber data yang digunakan adalah bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Teknik pengumpulan data yang digunakan adalah Studi kepustakaan (library research) dengan analisis data kualitatif. Hasil penelitian menunjukkan bahwa (1) Hukuman penjara yang dijatuhkan kepada terdakwa berdasarkan bukti-bukti yang ada di persidangan dan merujuk pada Pasal 81 ayat (2) Jo Pasal 76D UU RI Nomor 35 tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak Jo UU RI Nomor 17 tahun 2016 tentang Penetapan Peraturan Pemerintah Pengganti UU No. 1 tahun 2016 tentang Perubahan Kedua Atas UU RI No. 23 Tahun 2002 Tentang Perlindungan Anak Jo UU No. 11 tahun 2012 tentang Sistem Peradilan Anak. (2) Pada putusan perkara ini majelis hakim telah mempertimbangkan dasar mengadili, dasar memutus, dimana Syarat-syarat untuk menjatuhkan sanksi pidana telah terpenuhi.